Topical Application of Dipyridamole and Roflumilast Combination Nanoparticles Loaded Nanoemulgel for the Treatment of Psoriasis in Rats - Maded ZK; Lassoued MA; Taqa GA; Fawzi HA; Abdulqader AA; Jabir MS; Mahal RK; Sfar S (International Journal of Nanomedicine, 2024)
Zeyad Khalaf Maded,1 Mohamed Ali Lassoued,1 Ghada Abd ‎Alrhman Taqa,2 Hayder Adnan Fawzi,3 Alaa Abdulelah Abdulqader,4 Majid S Jabir,5 Raffah Khamis Mahal,6 Souad Sfar7 1Laboratory of ‎Pharmaceutical, Chemical‎, and Pharmacological Drug ‎Development LR12ES09, ‎Faculty of Pharmacy, ‎University of Monastir, Monastir, Tunisia; 2Department of Dental Basic ‎Sciences, College of ‎Dentistry, University of ‎Mosul, Mosul, Iraq; 3Department of Pharmacy, Al ‎Mustafa University College, Baghdad, Iraq; 4Department of ‎Pharmaceutics, College of ‎Pharmacy, University of ‎Tikrit, Tikrit, Iraq‎; 5Department of ‎Applied ‎Science, University of ‎‎Technology, Baghdad, Iraq‎; 6Department of ‎Pharmaceutics, College of ‎Pharmacy, The University ‎of ‎Mashreq‎, Baghdad, 10023, ‎‎Iraq; 7Laboratory of Chemical, ‎‎Galenic and Pharmacological ‎‎Development of Medicines ‎‎‎(LR12ES09), Faculty of ‎‎Pharmacy of Monastir, ‎‎University of Monastir, Monastir, TunisiaCorrespondence: Hayder Adnan Fawzi, Email hayder.adnan2010@gmail.comBackground: Phosphodiesterase-4 is an enzyme that regulates immune responses and contributes to the development of psoriasis. Dipyridamole and roflumilast function as phosphodiesterase-4 inhibitors, reducing pro-inflammatory cytokine expression. The aim was to evaluate the anti-psoriatic effect of the topical administration of dipyridamole and roflumilast nanoemulgel combination on imiquimod-induced psoriasiform skin inflammation in rats.Methods: Dipyridamole and roflumilast were formulated into nanoemulgel to enhance skin penetration and retention. The production of nanoemulgels involves a two-part process. A nanoemulsion is created (the aqueous phase titration method was employed to create nanoemulsions‎), which is then incorporated into the gelling agent during the second phase. The new formula was then tested in rats. The rats were divided into seven groups; all animals were treated for 16 days. Induction was achieved by 120 mg of 5% imiquimod cream, which was applied daily for 8 days. After induction, groups received one of the following: 0.05% clobetasol ointment, 1% dipyridamole nanoemulgel (D-NEG), 0.3% roflumilast nanoemulgel (R-NEG), 1% dipyridamole and 0.3% roflumilast gel combination (DR-gel), and 1% dipyridamole and 0.3% roflumilast nanoemulgel combination (DR-NEG). At the end of the experiment, all animals were euthanized, and their blood and skin tissue samples were obtained. Inflammatory markers, immunohistochemistry, and histopathology were measured.Results: The DR-NEG group showed significantly lower levels of IL17, IL23, and TNF-α, while TGF-β showed higher levels than the clobetasol group. The expression of CK16 was significantly lower compared to the clobetasol group. DR-NEG showed a significantly lower PASI and Baker score than the clobetasol group.Conclusion: The new DR-NEG’s topical combination administration showed better anti-inflammatory, tissue healing, and anti-psoriatic activity than each drug alone or topical clobetasol administration; this could be attributed to the possible synergic effects of both drugs and the enhanced skin penetration offered by the nanoemulgel formulation. Keywords: dipyridamole, roflumilast, nanoemulgel, psoriasis, anti-inflammatory